Removal of Iron, Manganese, Cadmium, and Nickel Ions Using Brewers’ Spent Grain - Karina Haro Carrasco; Egon Götz Höfgen; Dominik Brunner; Konstantin B. L. Borchert; Berthold Reis; Christine Steinbach; Martin Mayer; Simona Schwarz; Karl Glas; Dana Schwarz (Polysaccharides, 2022)
The human-made pollution of surface and ground waters is becoming an inevitable and persistently urgent problem for humankind and life in general, as these pollutants are also distributed by their natural circulation. For example, from mining activities and metallurgy, toxic heavy metals pollute the environment and present material risk for human health and the environment. Bioadsorbers are an intriguing way to efficiently capture and eliminate these hazards, as they are environmentally friendly, cheap, abundant, and efficient. In this study, we present brewers’ spent grain (BSG) as an efficient adsorber for toxic heavy metal ions, based on the examples of iron, manganese, cadmium, and nickel ions. We uncover the adsorption properties of two different BSGs and investigate thoroughly their chemical and physical properties as well as their efficiency as adsorbers for simulated and real surface waters. As a result, we found that the adsorption behavior of BSG types differs despite almost identical chemistry. Elemental mapping reveals that all components of BSG contribute to the adsorption. Further, both types are not only able to purify water to reach acceptable levels of cleanness, but also yield outstanding adsorption performance for iron ions of 0.2 mmol/g and for manganese, cadmium, and nickel ions of 0.1 mmol/g.